Oral radiology: principles and interpretation - White, S. C. Stuart C. (Elsevier: Mosby, 2009)
With more than 1,000 high-quality radiographs and illustrations, this bestselling book visually demonstrates the basic principles of oral and maxillofacial radiology as well as effective clinical application. You'll be able to diagnose and treat patients effectively with the coverage of imaging techniques, including specialized techniques such as MRI and CT, and the comprehensive discussion of the radiographic interpretation of pathology. The book also covers radiation physics, radiation biology, and radiation safety and protection - helping you provide state-of-the-art care!